Design and Analysis of Battery Box Lifter - N, Karthick; S, Aravindh; N, Gayathri; N, Nagendran; K R, Siddaarthan; A, Thenamuthan (International Journal of Engineering and Technology, 2018)
The main objective of this project is to design and analyze the portable hydraulic scissor truck instead of manual pallet truck for the purpose of dropping and lifting battery box in AC Coaches to bring it outside for checking suspension/cradle of battery box for availability of all suspension bolts, signs of any cracks, corrosion, rusting and taking corrective action, if necessary. If suitable hydraulic cylinder with more power is used, this scissor lift can also be designed for heavy load purposes. This equipment will be simple to use. Frequent maintenance is not required for this equipment. In this paper we carried out detailed analysis of scissor mechanism members against bending and buckling failure and also focused on various design aspects and working of scissor mechanism and helpful to lifting and dropping of battery box without any failure with this scissor truck  For existing practice the battery box dropping and lifting done  by  using  manual  pallet  truck.  It  shows  the  design  is  unsafe  handling,  injury  to  employee  and  feel uncomfortable. It is very tedious for human being to lift a vehicle above from the ground. Even when a hydraulic jack is implemented, it requires manual work. In this era, every man in the world wants comfort and hence to relieve the problems faced by lifting and placing the battery box.  Our project aims to reduce the manual work involved during the replacement of battery box instead of applying manual pallet truck. To validate our point and to reduce the above said difficulties faced, the design of hydraulic lift has been changed.